2019
DOI: 10.1111/ijfs.14374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and PH value on the stability of bioactive compounds and antioxidative activity of juice from colour‐fleshed potatoes

Abstract: The colour-fleshed potatoes represent a good raw material for the extraction of juices with a high content of biologically active compounds and a high antioxidant activity. The blue-fleshed potatoes turned out to be a rich source of total polyphenols, as they had approximately 3.5 times higher content of identified anthocyanidins. Regardless of anthocyanin composition, all juices made of colour-fleshed potatoes were highly stable. Both, high temperature, exposure time to these temperatures, and medium pH had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The use of potatoes with purple-coloured flesh increased concentration of phenolic compounds in the beers, as well as the antioxidant activity of the beverages. As the main phenolic compounds in the beers originate from barley, which is not especially rich in phenolic compounds, changing part of the ‘grain bill’ of the beer for potatoes with purple-coloured flesh, which have been proven to possess high concentration of phenolic compounds, as well as high antioxidant activity (Rytel et al; Rytel et al; Lachman et al 34 ) ought to increase phenolic compound content, as well as increase beer antioxidant activity, which is confirmed by the results acquired in this study 2 , 31 , 39 41 . The increased concentration of chlorogenic acid, neochlorogenic acid and cryptochlorogenic acid, as well as anthocyanins is probably the main reason of the increased activity of the P30 and P50 beers, because these compounds have been proven in the past to be strong antioxidants 42 , 43 .…”
Section: Resultssupporting
confidence: 85%
“…The use of potatoes with purple-coloured flesh increased concentration of phenolic compounds in the beers, as well as the antioxidant activity of the beverages. As the main phenolic compounds in the beers originate from barley, which is not especially rich in phenolic compounds, changing part of the ‘grain bill’ of the beer for potatoes with purple-coloured flesh, which have been proven to possess high concentration of phenolic compounds, as well as high antioxidant activity (Rytel et al; Rytel et al; Lachman et al 34 ) ought to increase phenolic compound content, as well as increase beer antioxidant activity, which is confirmed by the results acquired in this study 2 , 31 , 39 41 . The increased concentration of chlorogenic acid, neochlorogenic acid and cryptochlorogenic acid, as well as anthocyanins is probably the main reason of the increased activity of the P30 and P50 beers, because these compounds have been proven in the past to be strong antioxidants 42 , 43 .…”
Section: Resultssupporting
confidence: 85%
“…The authors (Rytel et al. 2020 ; Tajner‐Czopek et al. 2008 ) also emphasize that further technological stages used in the production of fried or dried potato products contribute to the loss of glycoalkaloids to a lesser extent.…”
Section: Introductionmentioning
confidence: 99%
“…Based on research conducted by other authors (Rytel et al 2013), it can be concluded that removing the potato skin in the process of peeling them, or, as in the production of juices, by separating the potato pulp during its production, from 50% to 70% of glycoalkaloids can be removed. The authors (Rytel et al 2020;Tajner-Czopek et al 2008) also emphasize that further technological stages used in the production of fried or dried potato products contribute to the loss of glycoalkaloids to a lesser extent.…”
mentioning
confidence: 99%
“…Potato anthocyanins include acetylated cyanidin derivatives, with colors ranging from orange to red, blue, and violet, depending on the pH of the environment [4,6,7]. Potatoes contain water-soluble anthocyanins, which are stable in acidic environments, including pigments isolated from fruit, as well as in neutral or slightly alkaline environments [8,9]. Plant pigments are very unstable, and their activity can change depending on pH, temperature, presence of metal ions, or oxygen [10,11].…”
Section: Introductionmentioning
confidence: 99%